(untitled) (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2026)
Social media has become part of adolescents’ daily life as it has revolutionized communication and connectivity, offering opportunities for self-expression, information dissemination, and social interaction. Meanwhile, students’ psychosocial development drastically changed as these technologies continue to proliferate, affecting various aspects of their life. This study aimed to determine the influence of social media engagement to the psychosocial development of students leading to the creation of promotional material focused on responsible social media use. This quantitative study uses descriptive-correlational research design to survey 204 Senior High School students chosen through simple random sampling. The researchers utilized weighted mean and standard deviation to describe their level of social media engagement and psychosocial development. Regression analysis determined the influence of social media engagement on psychosocial development. It was found that students have high engagement on their social media platform usage, and social media content consumption, while screen time limits are lower indicating that they know when to stop using it. The respondents also perceive social media to be highly influential in their psychosocial development, which was later confirmed by the regression analysis. The results imply that engaging with social media can shape how the social behavior of a person develops. While social media lets the respondents express themselves and connect with others, using it too much could harm their wellbeing. The study recommends the adoption of an advocacy video for a responsible social media use campaign, to address diverse psychosocial challenges arising from social media interactions among the students.